Phase controlled synthesis and characterization of noble metal nanomaterials - Fan, Zhanxi (2015)
Noble metal nanomaterials have received extensive research interest owing to their unique physical and chemical properties, and various important applications like energy conversion and storage, surface enhanced Raman scattering (SERS), electronics, bioimaging and biosensing, information storage, photo- and electro-catalysis. Recently, it was found that the physical and chemical properties of noble metal nanomaterials can be greatly influenced by their crystal structures. Therefore, it is of paramount importance to develop new method/strategy for the efficient and facile synthesis of new noble metal nanomaterials with controlled crystal phase. To realize this objective, the following researches have been conducted. Firstly, a ligand exchange method has been established for the shape and phase controlled synthesis of novel Au nanomaterials. By simply mixing the freshly prepared octadecanethiol (ODT) solutions with hexagonal close-packed (hcp) Au square sheet (AuSS), a unique hcp-to-face-centered cubic (fcc) phase transition is observed under ambient conditions, leading the formation of (100)f-oriented fcc AuSSs. It is worthy to point out that the phase change of inorganic nanomaterials is usually realized at extreme conditions, such as high pressure and high temperature. Importantly, during the process of ligand exchange mediated synthesis, the crystallinity degree of the as-prepared fcc AuSSs can be well modulated by changing the concentration of ODT molecules. Besides ODT, many other kinds of thiol molecules can also result in the formation of fcc AuSSs from the hcp AuSSs. Remarkably, monochromated electron energy loss spectroscopy (EELS) of individual fcc AuSSs reveals a strong localized surface plasmon resonance (LSPR) absorption in the infrared range. Secondly, the metal coating approach has been used for the synthesis of ultrathin noble bimetallic nanosheets (thickness < 5 nm) with controlled shape, structure and composition. Via the solution deposition of Ag onto hcp AuSSs in the absence of oleylamine, (100)f oriented fcc Au@Ag square sheet has been prepared. In contrast, polytypic hcp/fcc Au@Ag square sheet with an orientation of (110)h/(101)f is synthesized via the epitaxial growth Ag on hcp AuSSs in the presence of oleylamine. Besides, the synthesis of ultrathin fcc Au@Pt rhombic nanosheets has been realized via the epitaxial seeded growth of Pt on the hcp AuSSs at ambient conditions. Importantly, the as-prepared fcc Au@Pt rhombic nanosheets show an unusual orientation of (101)f. Significantly, by changing Pt to Pd, (101)f oriented fcc Au@Pd rhombic nanosheets can also be obtained from the hcp AuSSs. Interestingly, a tiny amount of (100)f oriented fcc Au@Pd and Au@Pt square nanosheets are found to be coexisting with the as-prepared Au@Pd and Au@Pt rhombic nanosheets, respectively. Moreover, monochromated EELS of individual fcc Au@Ag square sheets reveals a strong LSPR absorption in the infrared range. Thirdly, the high-yield colloidal synthesis of Au nanoribbons (NRBs) with the 4H hexagonal crystal structure, a novel polytype of Au, has been demonstrated. Note that Au usually crystallizes in the common fcc phase. The as-prepared Au NRBs have a thickness of 2.0–6.0 nm, width of 15.0–61.0 nm and length of 0.5–6.0 μm. Interestingly, the Au NRB undergoes a phase change from the initial 4H to fcc structures after ligand exchange under ambient conditions. Monochromated EELS of individual 4H Au NRBs reveals a strong LSPR absorption in a wide range of infrared region. Importantly, the epitaxial growth of other noble metals, e.g. Ag, Pt and Pd, on 4H Au NRBs can induce the structure transformation of Au NRBs from 4H to polytypic 4H/fcc structures, resulting in the production of noble bimetallic 4H/fcc Au@Ag, Au@Pd and Au@Pt core-shell nanostructures, respectively. The unprecedented synthesis of 4H Au NRBs and their derivative nanostructures will provide new opportunities for the phase-controlled synthesis of new advanced nanomaterials which may have a wide range of promising applications.